1967
DOI: 10.1126/science.158.3803.924
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin from Ultimobranchial Glands of Dogfish and Chickens

Abstract: Acid extracts of thyroid glands from a small shark Squalus suckleyi and domestic fowl Gallus domestica contained no detectable calcitonin activity, while very potent hypocalcemic responses were obtained in rats with similar extracts from the ultimobranchial glands of these two species. The calcitonin concentration was 4 to 40 times that present in hog thyroid, which, as in most other mammals, contains ultimobranchial tissue. The evidence suggests that calcitonin is a fundamental calcium-regulating hormone pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…Estimates of the relative contributions to thyroid weight from the lateral anlage range from less than 1 to 30% in humans [7]. In non-mammal vertebrates, the embryonic thyroid and UBB develop as separate structures, thus, C cells are confined to the ultimobranchial glands derived from the UBB, where they secrete calcitonin [8].…”
Section: Embryological Development Of the Thyroid Gland And Origin Ofmentioning
confidence: 99%
“…Estimates of the relative contributions to thyroid weight from the lateral anlage range from less than 1 to 30% in humans [7]. In non-mammal vertebrates, the embryonic thyroid and UBB develop as separate structures, thus, C cells are confined to the ultimobranchial glands derived from the UBB, where they secrete calcitonin [8].…”
Section: Embryological Development Of the Thyroid Gland And Origin Ofmentioning
confidence: 99%
“…Nonidez reported the presence of argyrophilic cytoplasmic granules C-cells and also remarked on their para-follicular location; he also hypothesized that these cells may have endocrine function (1). The term "calcitonin" was first coined by Copp and Cheney in as a substance of parathyroid origin as it was responsible for lowering serum calcium levels (2). The thyroid origin of calcitonin was first confirmed by Hirsch in 1963 andFoster in 1964 (3,4).…”
Section: Historical Perspectivementioning
confidence: 98%
“…Concerning the secretory functions of the ultimobranchial body, WATZKA (1933) suggested the possibility of an endocrine function for this organ, and CoPP et al (1967) reported the secretion of calcitonin based on their experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the ultimobranchial body of mammals, that of lower vertebrates-including birds-remains independent of the thyroid gland after birth, being involved in the secretion of calcitonin, similar to the parafollicular cells (DUDLEY, 1942;SEHE,1960;CoPP et al, 1967;CHAN et al, 1969). PEARSE (1966PEARSE ( , 1968PEARSE ( , 1969 has long been advocating the amine precursor uptake and decarboxylation (APUD) theory by noting the existence of serotonin (5-HT), an amine, in addition to calcitonin in the parafollicular cells and the ultimobranchial body.…”
Section: Discussionmentioning
confidence: 99%